Malawi : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report ;, 2006)
This paper presents Malawi's First Review Under the Poverty Reduction and Growth Facility. The overvalued exchange rate has put external reserves under pressure, and the backlog of unpaid import invoices persists. The impact of the overvalued exchange rate on the value of donor inflows and the unforeseen upward revisions to debt obligations has increased domestic borrowing needs. The government is committed to program implementation, but faces intense political pressures because of its minority position in parliament.